Recommendations to rejuvenate river Bharathapuzha using GIS and watershed simulation model - AISWARYA K. P; Fathima Shimji; Jishitha Ravindran; Nitha K; Rani P. R; Er. K. K Sathian (Guide) (Tavanur 2009 Department of Land and Water Resources and Conservation Engineering)
the main objectives of the study include modeling the topography of the river basin using GIS, to study existing flow pattern using wastershed simulation model and to suggest suitable interventions to improve the summer flow regime of river Bharathapuzha.
Recommendations to rejuvenate river Bharathapuzha using GIS and watershed simulation model